Development and Formation of Media-Competence in Teaching Foreign Languages - Sharofovna, Jabborova Dilafruz (Researchparks Publishing, 2023)
The article focuses on the study of the urgent issue of foreign language education in the light of the growing growth of digital media resources. The main characteristics of this environment are globalization, computerization, technologization, intercultural communication. It is the multiplicity of digital languages and cultures, the multiplicity of texts and document formats circulated in the global information environment, as well as the new forms of distributed (online) communication that decide the formation of a new consistency in an individual, the internet competence of a secondary language identity, a feature that facilitates the functionality of a single world machine.